The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1002/(sici)1521-4109(199809)10:12<857::aid-elan857>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Arsenic in Zinc Oxide Used as a Feed Additive

Abstract: Cathodic stripping voltammetry at a hanging mercury drop electrode was applied for determination of arsenic in samples of zinc oxide intended for use as a feed additive. The determinations were carried out in acidic medium in the presence of Cu(II). The As(V) was prereduced to As(III) by potassium iodide and ascorbic acid at ambient temperature. The detection limit was 0.1 ng mL−1. The feasibility of simultaneous determination of arsenic and cadmium in such analysis was also shown. The electrothermal atomic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…DP ASV was used for determination of cadmium and lead. For arsenic the use of DP CSV requires removal of HNO 3 before determination [4,5]. Because of reports of losses of arsenic during heating of samples at 150°C after addition of 0.2 mL H 2 SO 4 in the presence of HF [12], for soils C, D, and reference material an investigation was conducted to determine whether digestion with HNO 3 and HClO 4 is possible without addition of HF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DP ASV was used for determination of cadmium and lead. For arsenic the use of DP CSV requires removal of HNO 3 before determination [4,5]. Because of reports of losses of arsenic during heating of samples at 150°C after addition of 0.2 mL H 2 SO 4 in the presence of HF [12], for soils C, D, and reference material an investigation was conducted to determine whether digestion with HNO 3 and HClO 4 is possible without addition of HF.…”
Section: Resultsmentioning
confidence: 99%
“…A Princeton Applied Research 264 A polarographic analyzer equipped with an X-Y recorder (RE 0150 PAR), Polarecord E-504 (Metrohm), and the electrode system HMDE as working electrode, saturated Ag/AgCl as reference electrode, and Pt-wire as an auxiliary electrode, was used for voltammetry Cathodic stripping voltammetry for determination of arsenic was performed according to a procedure described elsewhere [4,5]. Sample solution (approx.…”
Section: Voltammetric Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic determination in those conditions depends on the number of factors such as: the copper concentration, time and the deposition potential, the concentration of supporting electrolyte and its pH. This system was studied by Kowalska and Golimowski [9,10]. Recently Piech et al [21] showed that this method has unique dependence on hydrodynamic conditions during deposition step.…”
Section: Introductionmentioning
confidence: 99%